'Nudging' as an architect of more responsible consumer choice in food service provision: The role of restaurant menu design. (15th February 2017) - Filimonau, Viachaslau; Lemmer, Christian; Marshall, David; Bejjani, Gisel
Abstract: The sector of food service provision generates substantial environmental and societal impacts. Environmental impacts are particularly pronounced in terms of carbon footprint build-up while societal impacts are reflected in often unhealthy food choice. These impacts should be minimised to facilitate progress of the sector towards sustainability. A significant share of the negative impacts from food service provision is attributed to irresponsible consumer choice which needs to be architected and made more society- and climate-benign. Customer 'nudging' is an effective tool of consumer choice architecture and yet little research has examined its application within the context of private food service provision. This study set to better understand the determinants of consumer choice when dining out and how consumer choice could be reinforced to make it more beneficial from the sustainability viewpoint. To this end, the study reported on the outcome of a consumer survey conducted among visitors to a UK casual dining restaurant where menu design was employed as a customer 'nudging' tool. The survey demonstrated that, next to price, food provenance and nutritional value determined consumer choice when dining out. This information should therefore be displayed on restaurant menus to enable educated, and more environment- and society-benign, food choice. While presenting the food carbon values on a menu was well perceived, some skepticism attached to their prospective use as a determinant of consumer choice was recorded. Recommendations were made on the design of the industry and policy-making interventions required to enhance the public appeal of this menu item. Highlights: 'Nudging' can enable more responsible consumer choice. We explore the application of 'nudging' in private food service provision. Determinants of more responsible consumer choice are identified. The potential of food carbon intensity values to inform consumer choice is revealed. The importance of menu design as a 'nudging' tool is demonstrated.